DAMPAK PENGGUNAAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DENGAN KEMAMPUAN MEMBACA SISWA MI MUHAMMADIYAH 01 CIPUTAT - Lutfi; Farihen; Laily Nurmalia; Abdul Latif; Hafidah Aribah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the Cooperative IntegratedReading and Composition (CIRC) model in improving reading comprehensionskills among fourth-grade students at MI Muhammadiyah 01 Ciputat. Employing aquantitative approach with a quasi-experimental design, the research involved twogroups: an experimental group that received instruction using the CIRC model anda control group that experienced conventional teaching methods. The results ofthe analysis revealed a significant improvement in the reading comprehensionabilities of students in the experimental group, as indicated by the comparison ofpretest and posttest scores. The CIRC model effectively fosters active studentparticipation, enhances group collaboration, and deepens text comprehensionthrough integrated activities such as reading, group discussion, and writing.Therefore, CIRC can be considered an engaging and meaningful alternativeteaching strategy for Indonesian language learning at the elementary level